Mockery and secretism in the social world of Mark's gospel - Neufeld, Dietmar (London New York Bloomsbury T & T Clark, 2014)
"Having established the context of mockery and shame in Ancient Mediterranean cultures, Dietmar Neufeld shows how Mark presented Jesus as a person with a sense of honour and with a sense of shame, willing to accept the danger of being visible and the mockery it attracted. Neufeld also considers the social functions of ridicule/mockery more broadly as strategies of social sanction, leading to a better understanding of how social, religious, and political practices and discourse variously succeeded or failed in Mark. Finally, Neufeld investigates the author of Mark's preoccupation with 'secrecy', showing that the author of Mark's disposition to secrecy in his narrative heightened when the dangers of scorn and ridicule from crowds or persons became pressing concerns. In a fiercely competitive literary environment where mocking and being mocked were ever present dangers, Mark, in his pursuit of authority gains it by establishing a reputation of possessing authentic, secret knowledge. In short, the so-called secrecy motif is shown to be deployed for specific, strategic reasons that differ from those that have been traditionally advanced."--Bloomsbury Publishing
Preface -- Acknowledgments -- Abbreviations -- Introduction -- 1. Modes of Mocking and Being Mocked in the Graeco-Roman World -- 2. The Messianic Secret in Recent Studies -- 3. Secretism and Mockery -- 4. Mark's Gospel as Narrative in Real Time: Chronicle, Mimesis and Plot -- 5. Mark, Mockery, Secretism, and Jesus: Markery...the Art of Telling a Good Story -- Ancient Sources Index -- Subjects Index -- Authors Index
Includes bibliographical references (pages 185-197) and indexes
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jesus Christ -- Humiliation; Jesus Christ; Bible -- Criticism, interpretation, etc; Bible; RELIGION ; Biblical Studies ; Jesus, the Gospels & Acts; RELIGION ; Biblical Studies ; New Testament; Humiliation; Criticism, interpretation, etc